Pengaruh Knowledge Management Dan Organizational Learning terhadap Organizational Effectiveness (Studi pada PT Surya Madistrindo Malang) - Kusuma, I Made Permadi (Universitas Brawijaya, Indonesia, 2013)
This study aims to analyze and explain the influence of Knowledge Management and Organizational Learning on Organizational Effectiveness company. This study reveals the influence of Knowledge Management on Organizational Effectiveness employees, as well as the influence of Knowledge Management on Organizational Effectiveness Organizational employees PT.Surya Madistrindo through Learning. Sample size was 73 respondents as employees PT.Surya Madistrindo Malang. Data retrieved using direct survey method with a questionnaire instrument. The questionnaires were distributed to 73 participants. Of the returned surveys, 54 questionnaires were fully completed. The response rate was 74 percent. This research used a path analysis model to test the hypothesis. Research findings show that Organizational Knowledge has positive effect on Knowledge Management. On the other hand, Knowledge Management is not yet able to achieve Organizational Effectiveness as PT Surya Madistrindo expectation. Also found the influence of Knowledge Management on Organizational Learning which will ultimately have an impact on the achievement of Organizational Effectiveness.